TheEffecntof Giving Furfures Soybean Tempeh NuggetTowardReducing Cholesterol Levelof White RatBlood(RattusNorvegicus) Hypercholesterolemia - Sufiati Bintanah; Erma Handarsari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2016)
Abstract. Coronary heart disease becomes a major cause of death because of the increase of cholesterol level in blood.Tempe and bekatulare said to be able to reduce blood fat levels. Problem: Howis the effect of Furfures Soybean TempeNugget oncholesterol levels of white ratRattusnurvegicushypercholesterolemiablood.Objective: To demonstrate the effect of Furfures Soybean Nugget on cholesterol levels of white rats Rattusnurvegicus hypercholesterolemia blood.Method: using laboratory experimental design with Randomizet Pre and Post Contro -group Only in hypercholesterolemia mice. The micewere given nugget 25%, 50%, 75% and Controlled for 21 days. The statistical analysis in this study was different test of Anova (analysis of varian) and continued with Benferoni test. The result shows that there is a significant gap of decreasing cholesterol level between controlled group with treatment 1, 2, 3 but it was not significant between the treatment 1,2 and 3. It can be concluded that giving Furfures Soybean Nugget can reduce cholesterol level in blood when it compared with not given treatment. Reducing cholesterol level with 1, 2, 3 treatmentsare not different significantly.